GENE-26. HOST GENETIC VARIATIONS IN MACROPHAGE MIGRATION INHIBITOR FACTOR CONFER WORSE PROGNOSIS IN GLIOBLASTOMA. (11th November 2019) - Otvos, Balint; Grabowski, Matthew; Alban, Tyler; Golubovsky, Joshua; Neumann, Chase; Rabjlenovic, Anja; Bayik, Defne; Lauko, Adam; Bucala, Richard; Vogelbaum, Michael; Lathia, Justin
Abstract: Genetic and systemic prognostic factors have been identified in glioblastoma (GBM) that correlate with survival, but patient-specific genomic risk factors that impact prognosis or response to immunotherapies have not been elucidated. GBM promotes an immune suppressive microenvironment via many mechanisms including the production of macrophage migration inhibitory factor (MIF) by GBM cancer stem cells, which activates myeloid derived suppressor cells (MDSCs). Increased circulating and intracranial MDSCs as well as intratumoral MIF expression in GBM patients portend a worse overall prognosis. Endogenous MIF expression is dependent on two genetic microsatellite loci: single nucleotide polymorphisms (SNPs) and CATT repeats within the promoter. To determine whether these genetic variations were linked to GBM development and/or prognosis, we assessed peripheral nucleated blood from 520 GBM patients for the MIF SNPs and CATT repeats. MIF microsatellite frequencies were similar between the normal population and GBM patients indicating loci variability was not a risk factor for GBM development. However, newly diagnosed IDH wild-type GBM patients with a minor allele SNP who received standard of care therapy had a 3.1 month shorter progression free survival (PFS), and a 4.3 month shorter overall survival (OS) when compared to patients with two major allele SNPs. This association was seen also with the CATT-repeat analyses. Furthermore, in a multivariate analysis for PFS that included age, sex, Karnofsky performance status, MGMT methylation status, 1p/19q co-deletion, and SNP status as covariates, only age and SNP status were independently associated with shorter PFS. Taken together, patients with variant MIF microsatellite loci experienced shorter PFS and decreased OS compared to those with the most common loci. These results are currently being validated in a separate 1700 patient cohort with the intent of understanding how MIF expression influences myeloid populations within the GBM microenvironment and then developing novel peripheral GBM screening markers for aggressiveness.